ANALISIS DESKRIPTIF STRATEGI DIVERSIFIKASI PRODUK PADA AKUN MEDIA SOSIAL @INDOMUSIKGRAM - Mevlied Tenri Nahla (Kartala Virtual Studies, 2024)
Product diversification is an effort to create new products with the aim of developing a business. This research describes the horizontal product diversification strategy carried out by the Instagram account @indomusikgram as the largest Instagram music community in Indonesia. This research is a descriptive qualitative research. The research method used is an open interview method. Data analysis carried out includes data presentation and drawing conclusions. The results of this study indicate that the @Indomusikgram account diversifies content in the form of 1) Re-uploading music videos, 2) #IMGNews, 3) Memes, 4) Events, and 5) Competitions/Challenges. Since @indomusikgram has been supervised by PT. BAKAT KREASI MUSIK DAN VISUAL (Indomusik Group), product diversification includes broader services such as 1) Media network, 2) Media production, 3) Intellectual Property, 4) Talent network, 5) Event network, and 6) Commerce Network . Based on these data, the @indomusikgram account under PT. BAKAT KREASI MUSIK DAN VISUAL is diversifying horizontally to accommodate services in the music industry with a similar target market, namely people who have an interest and involvement in the music industry in Indonesia.